A Response to Three Discussions of My Professional Work and Thought - Hargrove, Eugene C. (Environmental ethics, 2024)
I do not have any significant criticisms of the papers in this issue by Samantha Noll, Shane Epting, and Shan Gao. However, as a response, I can provide some discussion of how my views came to be and what remains unfinished near the end of my career.